Terminating Hyperinflation in the Dismembered Habsburg Monarchy - Wicker, Elmus (American Economic Review, 1986)
To assess the validity of Thomas Sargent's claim that hyperinflation can be terminated without dire employment effects, monthly unemploymentpercentage estimates were constructed for Poland, Hungary, and Austriaover the period both before and after monetary stabilization followingWorld War I. These data reveal that there were significant effects onemployment in the three territories. Unemployment peaked in Poland at alittle less than 13 percent; in Hungary at 12 percent and probably higher; and in Austria at 7 percent. An attempt is made to identify those considerations that contributed to the emergence of unemploymentwith the advent of monetary stabilization. Copyright 1986 by American Economic Association.